Recurrent multifocal adult rhabdomyoma in an elderly woman diagnosed with Birt-Hogg-Dubé syndrome: A case report - Andersen, Ulrik Ørsø; Rosenørn, Marie Røsland; Homøe, Preben (Frontiers in Surgery, 2022)
Birt-Hogg-Dubé syndrome (BHD) is a rare inherited autosomal dominant condition caused by a mutation in the tumor suppressor gene FLCN. This mutation predisposes the carrier to multiple pulmonary cysts, recurrent pneumothorax, renal tumors and benign skin tumors. Since the first description of BHD, additional clinical signs have been added to the syndrome and a large variety of benign tumors, such as rhabdomyomas (RM), have been linked with the FLCN gene mutation. RMs are rare tumors derived from striated muscle. The adult extracardiac rhabdomyoma occurs mostly in elderly patients, with a male predominance. It is most often located in the head and neck area and it has a potential of recurrence. We report a case of recurrent multifocal ARM in the oral cavity, present in an elderly woman with BHD and treated surgically. This could add support to RMs being linked to BHD.